Implicit learning of between-group intervals in auditory temporal structures - Terry, J.; Stevens, C. J.; Weidemann, G.; Tillmann, B. (Attention, perception & psychophysics, 2016)
Implicit learning of temporal structure has primarily been reported when events within a sequence (e.g., visual-spatial locations, tones) are systematically ordered and correlated with the temporal structure. An auditory serial reaction time task was used to investigate implicit learning of temporal intervals between pseudorandomly ordered syllables. Over exposure, participants identified syllables presented in sequences with weakly metrical temporal structures. In a test block, the temporal structure differed from exposure only in the duration of the interonset intervals (IOIs) between groups . It was hypothesized that reaction time (RT) to syllables following between-group IOIs would decrease with exposure and increase at test. In Experiments 1 and 2 , the sequences presented over exposure and test were counterbalanced across participants (Pattern 1 and Pattern 2 conditions). An RT increase at test to syllables following between-group IOIs was only evident in the condition that presented an exposure structure with a slightly stronger meter (Pattern 1 condition). The Pattern 1 condition also elicited a global expectancy effect: Test block RT slowed to earlier-than-expected syllables (i.e., syllables shifted to an earlier beat) but not to later-than-expected syllables. Learning of between-group IOIs and the global expectancy effect extended to the Pattern 2 condition when meter was strengthened with an external pulse (Experiment 2 ). Experiment 3 further demonstrated implicit learning of a new weakly metrical structure with only earlier-than-expected violations at test. Overall findings demonstrate learning of weakly metrical rhythms without correlated event structures (i.e., sequential syllable orders). They further suggest the presence of a global expectancy effect mediated by metrical strength.